Union wage effects - Alex Bryson (IZA World of Labor, 2014)
Despite declining bargaining power, unions continue to generate a wage premium. Some feel collective bargaining has had its day. Politicians on both sides of the Atlantic have recently called for the removal of bargaining rights from workers in the name of wage and employment flexibility, yet unions often work in tandem with employers for mutual gain based on productivity growth. If this is where the premium originates, then firms and workers benefit. Without unions bargaining successfully to raise worker wages, income inequality would almost certainly be higher than it is.
Keywords: J30; J31; J32; J50; J51; M54; 330; trade unions; wages; bargaining; labor market; firm performance; productivity